The Effects of TGfU, SEM and HTGfU-SEM Towards Volleyball and Badminton Cognitive Game Play on Performance Among Form One Students - MINHAT, NORALIZA; Jeganathan, Sanmuga Nathan; Salimin, Norkhalid (Advances in Social Sciences Research Journal, 2019)
The purpose of this study was to investigate the effects of Teaching games for Understanding (TGfU) as a control group compared to Sport Education Mode (SEM)l and Hybrid TGfU and Sport Education Model (HTGfU – SEM) as treatment groups in volleyball 3 vs 3 and badminton doubles game play. The effectiveness of these models were assessed based on cognitive tactical decision making of opening and closing space, selection of skill off digging, setting, blocking and spiking 3 vs 3 volleyball game play. As well as in opening and closing space and selection skills of forehand, lob shot and smash in badminton doubles game play. The research employed Quasi Experimental pre-post test design. A total of 96 students aged 13 years old were chosen intactly and distributed equally into three groups with 16 girls and 16 boys. The study utilized adopted Game Performance Assessment Instrument (GPAI) to access cognitive aspects of decision making. The data were analyzed using Mean, SD, ANOVA, ANCOVA, MANOVA and post-hoc test. As for the overall tactical decision making via multivariate test in volleyball and badminton double game play indicated significant through SEM. Especially for closing space in volleyball 3 vs 3 game play through SEM, F (2, 93) = 10.054, p < 0.05, η2 = .178. As well as significant improvement with SEM in opening space badminton double game play, with F (2, 93) = 3.148, p < 0.05, η2 = 0.63. Furthermore pairwise comparison indicated improvement through SEM for closing space with SEM, p = 2.031, p < 0.05. Therefore SEM is recommended as game play model for future learning cognitive aspects of tactical decision making in volleyball and badminton.